Pengembangan Konsep Cleaner Drilling Berdasarkan Studi Kasus Pengeboran Minyak Di Perusahaan “XXX” Menggunakan Pendekatan FMEA - Haryono Haryono; samsudin affandi; Gatot Subroto (Institut Teknologi Adhi Tama Surabaya, 2022)
ABSTRACT In the oil and gas industry, from planning to drilling to closing oil fields, it has the potential to cause impacts and needs to be addressed. One of the efforts to handle the impact proposed the concept of